The Cathepsin Family in Disease: From Molecular Mechanisms to Therapeutic Applications - Alzoubi, Lorca; Hamzat, Yassmen; Alqudah, Alaa; Aljabali, Alaa A.A. (Current Neuropharmacology, 2025)
T4he cathepsin family of proteolytic enzymes is involved in the maintenance of major physiological processes, including protein degradation, immune modulation, tissue remodeling, and apoptosis. Members of the cathepsin family include cysteine, serine, and aspartic proteases, which are implicated in diverse cellular functions. Evidence for tissue-specific expression emphasizes the specialized functions of these enzymes in many organs. However, dysregulated cathepsin activity has been implicated in a wide range of pathological conditions, including, but not limited to, cancer, cardiovascular diseases, neurodegeneration, and autoimmune disorders. There is significant therapeutic potential for intervention, whereby specific inhibitors of certain cathepsins may offer promising strategies for disease management. Despite this promise, major challenges persist in designing inhibitors that avoid off-target effects while respecting the dual physiological and pathological roles of cathepsins. Structural similarities among family members and their context-dependent functions complicate precision targeting. This review identifies the emerging strategies including structure-guided design, cathepsin-cleavable delivery systems, and real-time imaging that are reshaping therapeutic approaches toward these complex enzymes. A structured web-based literature search was conducted using PubMed, Scopus, and Google Scholar employing keywords such as “cathepsins”, “therapeutic targeting”, “proteolytic enzymes”, and “disease pathways” to inform this review. As cathepsins continue to play a key role in health and disease, much research is warranted to determine their full therapeutic potential, which would represent a foundation for treatment options for various complex diseases.
Keywords: Cathepsins